Pengembangan Dashboard Interaktif Indeks Desa Membangun(IDM) Berbasis Web Provinsi Sumatera Selatan - Dwi Novanni, Windri; Nasir, Muhammad (BETRIK, 2026)
The Village Development Index (IDM) is an important instrument for assessing the level of development and independence of villages in Indonesia. Therefore, data covering social, economic, and environmental aspects need to be presented visually and informatively for easy understanding by various stakeholders. The system development used the Waterfall method, which includes sequential stages of needs analysis, design, implementation, testing, and maintenance. A dashboard was built to present data in the form of tables, graphs, and interactive maps. In addition, this dashboard is intended to be integrated and displayed on the "Bumi Sriwijaya Village" website owned by the Statistics Indonesia (BPS) of South Sumatra Province. The results of system testing using the Black Box Testing technique showed that all system functions run according to predetermined specifications without any functional errors. Thus, the developed dashboard is declared suitable for use as a tool in data-based village development planning, evaluation, and policy-making.